„Żyłem z wieszczem tym za młodu, jak brat z bratem…” – towarzyskie i poetyckie związki Januarego Poźniaka i Wincentego Pola - Klimek-Grądzka, Jolanta (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
This article discusses noticeable links between January Poźniak and Wincenty Pol as revealed in the poetry of the former. Poźniak’s poetic oeuvre – a Lviv lawyer and social activist, who always dreamt of becoming a poet – is an evident testimony of his lifelong friendship with Pol and his wife Kornelia. Poźniak touches upon such issues like Pol’s departure to Vilnius or his romantic affair with Kornelia – embedded in a folk symbolic framework. Poźniak’s works also reveal that both authors shared their sentiment for the fate of the nation. They also unveil Poźniak’s strong belief in Pole’s everlasting fame. Poźniak’s fascination with Pol – a poet and a national prophet – presents itself through his choice of vocabulary and his references to Pol’s poetic conventions, accompanied with a tendency to depreciate Poźniak’s own literary achievements (cf. motives of oblivion and the “rusty gusle”).